Effect of Gongronema Latifolium on lipid profile, oral glucose tolerance test and some hematological parameters in fructose-induced hyperglycemia in wistar rats - usenobong ufot; Idara Okon; Ufuoma Onoyeraye; Elvis Nwachukwu; Daniel Owu (Mazandaran University of Medical Sciences, 2019)
Gongronema latifolium (GL) has been used traditionally in the management of various ailments. The effects of GL on some haematological and biochemical parameters in fructose-induced hyperglycaemia were studied. Forty rats were randomly assigned to four groups of 10 rats each. Control was received normal rat chow, fructose + G. latifolium group was received 66% D-fructose mixed with 34% of feed daily. Fructose only group was received 66% D-fructose and the fourth group was received G. latifolium only respectively for 30 days. All animals were fed ad libitum and had free access to water. Oral blood glucose tolerance test was determined using 2 g/Kg in all groups of rats and blood samples were obtained by cardiac puncture for haematological and biochemical analyses. The blood glucose level was significantly raised in fructose-fed only group (140.6 ± 2.9 mg/dl) when compared to GL+fructose group (110.3 ±5.8 mg/dl) and control (88.1 ± 3.6 mg/dl). There was observed significant reductions in blood glucose and glucose tolerance following GL supplementation. The lipid profile values were significantly higher in fructose-fed group compared with other groups but these levels were significantly reduced following GL supplementation. The white blood cells (WBC) and platelets count in GL and fructose + GL group were significantly raised when compared with the control group. The red cell parameters were not significantly altered compared to the control group. The results show that the consumption of G. latifolium reduces hyperglycaemia and hyperlipidaemia hence the cardiovascular risk factors observed in diabetes mellitus.